2019
DOI: 10.24114/jik.v17i2.12299
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Tingkat Kecemasan (Anxiety) Dalam Menghadapi Pertandingan Atlet Sepak Bola Kabupaten Banyuasin Pada Porprov 2017

Abstract: Kecemasan menjadi situasi yang tergambar sangat jelas saat menjelang pertandingan, kecemasan tentu menjadi alasan terhadap buruknya performa atlet dilapangan, situasi demikian terjadi pada atlet sepak bola Kabupaten Banyuaisn menjelang Porprov 2017 di Palembang. Tujuan penelitian adalah untuk mengetahui faktor apa saja yang menyebabkan munculnya kecemasan (Anxiety), berapa besar tingkat kecemasan (anxiety) atlet sebelum bertanding. Metode penelitian yang digunakan dalam penelitian ini adalah kualitatif dan kua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 0 publications
0
9
0
18
Order By: Relevance
“…Athletes in competition often experience excessive feelings of anxiety [1]. Empirical evidence shows that 63% experience anxiety when competing [2]. Furthermore, it has been reported that more than 50 athletes competing in the Olympic events consulted with psychologists regarding their perceived anxiety complaints [3].…”
Section: Introductionmentioning
confidence: 99%
“…Athletes in competition often experience excessive feelings of anxiety [1]. Empirical evidence shows that 63% experience anxiety when competing [2]. Furthermore, it has been reported that more than 50 athletes competing in the Olympic events consulted with psychologists regarding their perceived anxiety complaints [3].…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety serves as a mechanism that protects the ego because anxiety signals to us that there is danger. Suppose the right action has not taken; the danger will increase until the ego is defeated (Kumbara, Metra, and Ilham: 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Kecemasan terjadi melalui runtunan peristiwa yang dimulai saat ada reaksi yang dialami baik intrinsik maupun ekstrinsik yang dianggap sebagai situasi yang membahayakan. Pandangan seseorang terhadap suatu kondisi berbahaya atau tidaknya itu dipengaruhi oleh kepribdian serta berdasarkan pada pengalaman yang dipelajari pada waktu lampau [10].…”
Section: Hasil Dan Pembahasanunclassified